57 An international historical cohort study of workers in the hard-metal industry. (11th October 2013) - Marsh, M; Buchanich,; Downing,; Kennedy,; Esmen,; Moshammer,; Morfeld,; Erren,; Svartengren,; Westberg,; McElvenny,; Cherrie,
Abstract : Objectives: In 2006, IARC found limited evidence in humans and sufficient evidence in animals that tungsten carbide (WC) with cobalt binder (WCCo) acted as a lung carcinogen (Group 2A). Our historical cohort study was designed to overcome certain limitations of earlier epidemiology studies by including a rigorous exposure assessment component, a nested case-control study of lung cancer and use of external and internal cohort rate comparisons. The primary research objectives include: To investigate the total and cause-specific mortality experience of current and former workers as compared with corresponding national and regional populations and internally-derived control groups, with adjustment for potential confounding factors and focus on lung cancer. To characterise the past and current working environment of subjects relative to work area, job title/function and potential for exposure to WCCo, as well as the component exposures: tungsten, tungsten carbide (without cobalt), carbon black, and cobalt; To determine the relationship between level and duration of exposures and lung cancer mortality with adjustment for potential co-exposures, including information obtained on tobacco smoking habits via a nested case-control study. Methods: Our cohort comprises 10 manufacturing sites in the United States and nine sites in Europe, and represents three companies, five countries (US, Austria, Germany, Sweden and UK) and multiple manufacturing processes. The study will include separate and pooled analyses. The epidemiological and exposure assessment components of the study are coordinated by the University of Pittsburgh and the University of Illinois at Chicago, respectively. The study is funded by the International Tungsten Industry Association; the US record collection phase was supported in part by the Pennsylvania Department of Health. Results: We will report on current progress in the US component of the study and in our efforts to coordinate the international study. Progress in the European studies will be reported separately by the respective investigators.